Bioactivity of Fungi from the Thousand Islands Against Staphylococcus aureus and Escherichia coli Using Dilution Method - Noverita Noverita; Samitri P. Debby (Universitas Nasional Jakarta, 2023)
The rapid advancement of science and technology has brought numerous benefits to human life; however, it is unfortunate that this progress has not extensively tapped into one of Indonesia's abundant biological resources, which is fungi, especially marine fungi. This research was conducted to explore the antimicrobial potential of marine fungi isolated from the Thousand Islands against Staphylococcus aureus and Escherichia coli using the dilution method. The study aimed to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the obtained isolates against the two test bacteria. The research comprised two phases: the collection of samples in the field, followed by the antimicrobial activity assay using the dilution method in the laboratory. The findings are expected to reveal several types of marine fungi from the Thousand Islands with antimicrobial capabilities that could be developed as alternative antibiotics to replace those that have lost their potency. The results of the study showed that out of the 10 tested marine fungi isolates, all of them exhibited inhibition against the growth of Staphylococcus aureus and Escherichia coli. The concentrations of 100% and 75% proved to be the most effective in inhibiting bacterial growth. The MIC of the tested marine fungi extracts was determined to be 25%. Moreover, five isolates of marine fungi demonstrated MBC against S. aureus and E. coli: S.KL5 isolate at concentrations of 75% and 50%, S.AL and S.KL1 isolates at concentrations of 100% and 50%, and S.MA2 and S.KL1 isolates at concentrations of 100% and 75%. The identified best isolates were found to belong to the species Penicillium sp. and Aspergillus niger .